Revisiting late Holocene sea-level change from the Gilbert Islands, Kiribati, west-central Pacific Ocean. Issue 3 (18th September 2017) - Yamano, Hiroya; Kayanne, Hajime; Yamaguchi, Toru; Inoue, Tomomi; Mochida, Yukira; Baba, Shigeyuki
Abstract: New coral microatoll data allow presenting an updated late Holocene sea-level curve for the Gilbert Islands of Kiribati. Examination of build-up elevation and spatial distribution of microatolls, along with radiocarbon age data from coral samples, suggest an approximately 1 m sea-level high stand, possibly lasting from 3500 to 1900 cal yr BP. Our sea-level curve, which is similar to the one reported from the Marshall Islands, is a baseline to reconstruct the evolution of reef flats and reef islands. In addition, it provides important contextual data to infer human settlement on islands in the west-central Pacific.